Analisis Disiplin Kerja berdasarkan Faktor Kepemimpinan dan Motivasi Implikasinya terhadap Kinerja Pegawai pada Sekretariat DPRK Bireuen - Erlinda, Erlinda; Bariah, Chairul; Mirza, Mirza; Fadhilah, Laina (Aceh Cooperative Care, 2025)
Performance is something expected by an institution. Measurable performance-based work is part of Human Resource Management. Employee performance is influenced by several factors. This study examines aspects of leadership, motivation, and work discipline. The study was conducted on 43 employees of the Bireuen DPRK secretariat. The research method used was an associative approach with a quantitative approach, and the problems were analyzed using path analysis. The results obtained were: (1) Work discipline is directly and indirectly influenced by leadership and work motivation, by 36.51% and 46.12%, respectively. (2) Simultaneously, leadership and work motivation contribute significantly to improving employee work discipline by 77.2%. (3) The implications for performance are 31.75% for leadership and 45.91% for work motivation. (4) Simultaneously, leadership and work motivation increase employee performance by 75.6%.